Infographic. Cooling strategies to attenuate PPE-induced heat strain during the COVID-19 pandemic - Bongers, C. C. W. G.; de Korte, J. Q.; Catoire, M.; Greefhorst, J.; Hopman, M. T. E.; Kingma, B.; Eijsvogels, T. M. H. (British Journal of Sports Medicine, 2021)
Physiologists evaluated many heat stress mitigation measures to improve athlete and military performance in challenging ambient conditions. Cooling interventions are known to improve exercise performance, decrease heat stress and enhance post-exercise recovery. Translating these concepts and solutions to medical science may attenuate heat stress and improve occupational performance for COVID-19 HCP. Similar knowledge transfer has previously been applied to minimise heat stress and extend work tolerance times in other occupational workers wearing protective clothing. Indeed, a previous study demonstrated that that cooling devices worn under PPE can decrease the physiological and subjective strain in a simulated hot and humid laboratory environment.